2021
DOI: 10.13057/biodiv/d220228
|View full text |Cite
|
Sign up to set email alerts
|

The allometric relationships for estimating above-ground biomass and carbon stock in an abandoned traditional garden in East Kalimantan, Indonesia

Abstract: Abstract. Karyati, Widiati KY, Karmini, Mulyadi R. 2021. The allometric relationships for estimating aboveground biomass and carbon stock in an abandoned traditional garden in East Kalimantan, Indonesia. Biodiversitas 22: 751-762. The existence of traditional gardens after abandonment process has a role based on ecological and economic aspects. To estimate the biomass and carbon stock in the abandoned traditional gardens, specific allometric equations are required. The aim of this study was to develop allometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
(38 reference statements)
0
9
0
1
Order By: Relevance
“…In the context of the destructive method, a representative sample is importantly required to obtain ideal information related to tree attributes. Most studies generally used diameter distribution since it could also describe the vegetation structure from the sampling location (Altanzagas et al, 2019;Istrefi et al, 2019;Karyati et al, 2021). Moreover, the diameter is a tree parameter that most accurate to measure.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the destructive method, a representative sample is importantly required to obtain ideal information related to tree attributes. Most studies generally used diameter distribution since it could also describe the vegetation structure from the sampling location (Altanzagas et al, 2019;Istrefi et al, 2019;Karyati et al, 2021). Moreover, the diameter is a tree parameter that most accurate to measure.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, tree height measurement had a high potential for bias due to the problematic situation for determining each species' top crown. Several studies also reported that tree diameter was the best predictor variable for constructing the allometric equation for community forests tree species (Karyati et al 2021;Wirabuana et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…However, equations for estimating this biomass and carbon stocks have been subjected to several disturbances, such as forest fires, shifting cultivation, and traditional gardens. Karmini et al (2021) showed a 50-year-old secondary forest in the Province of East Kalimantan, Indonesia, with unique characteristics differentiating it from other areas. For example, a 50-year-old secondary forest has many trees with Moraceae and Euphorbiaceae's most dominant families, with the Macaranga motleyana, Artocarpus elasticus, and Symplocos fasciculata species.…”
Section: Introductionmentioning
confidence: 99%